Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Talent Management terhadap Kinerja Karyawan - Syahril Asfiah Nurwahid; Epsilandri Septyarini (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to determine the effect of leadership style, organizational culture, and talent management on employee performance on KSPPS BMT Dana Insani Gunungkidul employees The method used in this study uses quantitative methods. The population in this study were employees who worked at KSPPS BMT Dana Insani Gunungkidul by using a sample of 34 respondents using a sampling technique, namely purposive sampling. The data analysis used is multiple linear regression analysis. The results showed that leadership style, organizational culture, and talent management have a positive and significant effect on employee performance. Thisresearch supports various theories which reveal that leadership style factors, and talent management have a significant role in shaping employee performance. Theimplications of this research are expected to improve employee performance.